Reformulasi Sistem Post Merger Notification untuk Menghindari Rechtvacuum Pembatalan Merger oleh KPPU - Muhammad Fadhali Yusuf (Komisi Pengawas Persaingan Usaha, 2022)
ABSTRACT The Post-Merger Notification system implemented in Indonesia today is certainly still causing controversy and debate among practitioners and academics, considering that this system allows Notification of Merger transactions only after the Merger is carried out. When compared with other countries, there are differences that certainly affect the application of Antitrust Law, which in other countries have implemented the Pre-Merger Notification system. The author in this study tries to examine the legal vacuum that exists in the Post-Merger Notification system and formulates efforts to improve the Post-Merger system. The research method used is normative juridical, with a conceptual approach and a statutory approach. Then the results obtained from the research that KPPU prepares and harmonizes regulations and schemes to cancel the merger transaction of a company that has carried out the merger as well as arrangements regarding the Restoration of the Legal Status of the Companies resulting from the Cancellation of the Merger. This is done in order to provide legal certainty for Business Actors as well as to improve the legal vacuum in the enforcement of Antitrust Law. Keywords: Legal Vacuum, Merger, KPPU